The things she's seen - Kwaymullina, Ambelin, 1975-; Kwaymullina, Ezekiel, 1983- (Alfred A. Knopf, 2019)
The ghost of a girl who recently died in an accident makes contact with her grieving father to help solve a mystery in a remote Australian town, where a girl who speaks entirely in riddles is the only witness to a fatal fire.